Sham sleep feedback delivered via actigraphy biases daytime symptom reports in people with insomnia: Implications for insomnia disorder and wearable devices - Gavriloff, D; Sheaves, B; Juss, A; Espie, CA; Miller, CB; Kyle, SD (Wiley, 2018)
This study investigated whether providing sham feedback about sleep to individuals with insomnia influenced daytime symptom reports, sleep‐related attentional bias and psychomotor vigilance. Sixty‐three participants meeting DSM‐5 criteria for insomnia disorder were recruited from the community. Following baseline assessments and actigraphy briefing, participants were randomised to receive next‐day sham feedback on sleep quality (“positive” vs. “negative” sleep efficiency condition). Feedback was delivered at habitual rise‐time using an integrated actigraphy‐diary watch to simulate wearable device behaviour. Participants completed symptom reports immediately before receiving feedback, and at 12:00 and 15:00 hr, using the experience sampling method. Following this they returned to the laboratory in the evening to complete symptom reports and computerised tests of sleep‐related attentional bias and basic psychomotor vigilance. Participants randomised to negative feedback (n = 32) evidenced impaired daytime function (decreased alert cognition [d = 0.79], increased sleepiness/fatigue [d = 0.55]) in the evening compared with those given positive feedback (n = 31). Within‐day trajectories revealed that the positive‐feedback group, relative to the negative‐feedback group, displayed a significantly greater increase in positive mood and alert cognition (from rise‐time to 12:00 hr), and significantly greater decrease in sleepiness/fatigue. There were no significant between‐group differences on measures of sleep‐related attentional bias [d = 0.20] or psychomotor vigilance [d = 0.12]. This controlled experiment shows that sham feedback about sleep biases appraisal of daytime symptoms, highlighting a pathway connecting sleep misperception with daytime features of insomnia. Findings have important implications for wearable devices that claim to measure “objective” sleep yet may provide inaccurate data relative to gold‐standard measurement.